NOG-Derived Peptides Can Restore Neuritogenesis on a CRASH Syndrome Cell Model - Matteo Gasparotto; Yuriko Suemi Hernandez Gomez; Daniele Peterle; Alessandro Grinzato; Federica Zen; Giulia Pontarollo; Laura Acquasaliente; Giorgia Scapin; Elisabetta Bergantino; Vincenzo De Filippis; Francesco Filippini (Biomedicines, 2022)
Homo- and heterophilic binding mediated by the immunoglobulin (Ig)-like repeats of cell adhesion molecules play a pivotal role in cell-cell and cell-extracellular matrix interactions. L1CAM is crucial to neuronal differentiation, in both mature and developing nervous systems, and several studies suggest that its functional interactions are mainly mediated by Ig2–Ig2 binding. X-linked mutations in the human L1CAM gene are summarized as L1 diseases, including the most diagnosed CRASH neurodevelopmental syndrome. In silico simulations provided a molecular rationale for CRASH phenotypes resulting from mutations I179S and R184Q in the homophilic binding region of Ig2. A synthetic peptide reproducing such region could both mimic the neuritogenic capacity of L1CAM and rescue neuritogenesis in a cellular model of the CRASH syndrome, where the full L1CAM ectodomain proved ineffective. Presented functional evidence opens the route to the use of L1CAM-derived peptides as biotechnological and therapeutic tools.